PENGARUH KREATIVITAS GURU MENGAJAR DAN MINAT BELAJAR SISWA TERHADAP PRESTASI BELAJAR SISWA SMK N 1 TANJUNG RAYA - Meli Puspa; M. Imamuddin; Rahmawati Rahmawati (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to determine (1) the influence of teacher creativity on student achievement, (2) the influence of student interest on student achievement, and (3) the influence of teacher creativity and interest in learning. Against student achievement at SMK N 1 Tanjung Raya. The type of research used in this research is quantitative correlative. Correlation studies aim to find out whether there is a relationship between two or more variables. The research population was students of class XI TKJ SMK Negeri 1 Tanjung Raya for the academic year 2022/2023, totaling 23 students. The sampling technique was carried out by random sampling. The method of data analysis in this study is partial regression analysis and multiple (simultaneous) regression analysis. The conclusions from this study are: (1) Teachers or educators with high educational creativity produce students who excel in mathematics, while teachers or educators with moderate or low creativity produce students who achieve below average in mathematics. (2). Students with high learning interest did better in mathematics than students with moderate or low learning interest. (3). Achievement (y) of 30.36% was influenced by the variables of teacher creativity (X1) and student learning interest (X2), while the remaining (100% - 30.36%) was 69.64% for other reasons. This shows that, at 30.36%, the teacher's creativity and interest in learning have a significant effect on students' mathematics learning achievement. What's more is that there are other factors that influence, but other factors are the influence of the environment, facilities, clubs and student motivation. Keywords: Teacher Teaching Creativity, Student Learning Interest, Student Achievement Results